2004
DOI: 10.1002/ldr.598
|View full text |Cite
|
Sign up to set email alerts
|

Growing three aromatic grasses in different alkali soils in semi‐arid regions of northern India

Abstract: Alkali lands in India occupy about 3 million ha. Due to poor physical properties, excessive exchangeable sodium and high pH, most of these lands support a very poor vegetation cover. Many of the medicinal and aromatic plants are in great demand for both internal requirements and export. But since these crops are non-conventional in nature, it is not always possible for them to be produced on fertile lands, which can be used for arable crops. The marginal lands, specifically the lands affected by salinity or so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 3 publications
4
23
0
Order By: Relevance
“…Although crop-based management of salt-affected soils has been in practice for decades in Iran and elsewhere in the world, there has been a renewed interest in this approach because in addition to soil amelioration there are economic incentives from the crops in terms of their market demand or farm level utilisation (Marcar et al, 2003;Dagar et al, 2004;Qadir and Oster, 2004). Additional benefits from crop-based interventions include improved nutrient availability status (Qadir et al, 2001) and carbon storage (Kaur et al, 2002) in the post-plantation soil.…”
Section: Crops and Crop-assisted Management Approachesmentioning
confidence: 96%
“…Although crop-based management of salt-affected soils has been in practice for decades in Iran and elsewhere in the world, there has been a renewed interest in this approach because in addition to soil amelioration there are economic incentives from the crops in terms of their market demand or farm level utilisation (Marcar et al, 2003;Dagar et al, 2004;Qadir and Oster, 2004). Additional benefits from crop-based interventions include improved nutrient availability status (Qadir et al, 2001) and carbon storage (Kaur et al, 2002) in the post-plantation soil.…”
Section: Crops and Crop-assisted Management Approachesmentioning
confidence: 96%
“…In a study that tried to develop management practices for growing vetiver under Mediterranean conditions (Dudai et al, 2006), it was found that once it was established, vetiver could survive the dry Mediterranean summer, although rain-fed plants were much shorter than irrigated ones. Dagar et al (2004) found that in semi-arid regions of northern India, that vetiver, which withstands both high pH and flooded conditions, could successfully be grown without significant yield reductions on highly alkaline soils.…”
Section: Introductionmentioning
confidence: 98%
“…Meanwhile, the mentioned relationship was very important for the analysis of the effect mechanisms of H 2 O 2 concentrations on metal removal. On the other hand, Cymbopogon schoenanthus L. Spreng (Lemon grass, LG) is widely indigenous in tropical and semi-tropical areas and has been found to be commercially biological resources (Dagar et al, 2004). However, there were no literatures on the use of LG as the source of hydrothermally carbonized sorbents until now.…”
Section: Introductionmentioning
confidence: 99%